Examining the Security Issues of Automated Teller Machine Based on Revised Technology Acceptance Model - Aida Fitriyani; Sfenrianto Sfenrianto; Gunawan Wang; Aries Susanto (Universitas Ahmad Dahlan, 2016)
Trust of using automated teller machine (ATM) is a daunting task for many Indonesians, where the security issues associated with it, still haunting them. The paper examines the collaborative issues related to the ATM security such as: perceived usefulness and ease of use, perceived security, trust, intention to use and actual system use, by using revised technical acceptance model (TAM) according to the banking purposes. The study takes customer samples of major leading banks in Indonesia and expected to present the current situation faced by many Indonesians when dealing with the ATM security. The outcome will be valuable inputs for the policy makers of the banks to establish further strategy to cope with integrated security issues related to ATM use.